Conversion rate and complications in laparoscopic cholecystectomy in acute versus chronic cholecystitis: a prospective cohort study - Ranga, Hans Raj; Vaishnavi; Arora, Bhavinder Kumar; Yadav, Dushyant Kumar; Tarun (International Surgery Journal, 2026)
Background: Laparoscopic cholecystectomy (LC) is the gold standard treatment for symptomatic gallstone disease. However, acute cholecystitis (AC) is traditionally considered more challenging than chronic cholecystitis (CC) due to edema, adhesions, and distorted anatomy in Calot’s triangle. These factors may increase operative time, conversion rates, and complication risks. With modern safety strategies such as the critical view of safety (CVS), outcomes may be comparable between the two conditions. Methods: A prospective cohort study was conducted including 70 patients undergoing LC, divided into two groups: 35 patients with AC and 35 with CC. Operative time, intraoperative difficulty, conversion to open surgery, postoperative complications, and hospital stay were compared. Results: The conversion rate was 5.7% in both groups. Operative time was marginally longer in AC but without statistical significance. Intraoperative bleeding, bile leak, wound infection, and subhepatic collection were slightly more frequent in the acute group; however, no statistically significant difference was observed. No major bile duct injury occurred in either group. Conclusions: LC in AC is safe and feasible when performed with adherence to standard safety principles. Conversion and complication rates are comparable to CC in experienced hands.